Sequential liver and kidney living donors: Making the ultimate gift twice. Issue 8 (28th June 2022) - Al Harakeh, Hasan; Emmanuel, Bishoy; Hughes, Christopher; Tevar, Amit; Steel, Jennifer Lynne; DiMartini, Andrea; Ganesh, Swaytha; Sood, Puneet; Humar, Abhinav
Abstract: There are nearly 150 living donors in the United States who donated more than one solid organ. Using our divisional database, we found 20 individuals who donated a liver and a kidney at different times. We performed a retrospective chart review of these donors, studying their motivating factors, complications and outcomes. The donors included 11 (55%) males and nine females. Thirteen (65%) donated the kidney before the liver. Fourteen (70%) were nondirected donors at the first donation, and four of the six directed donors in the first donation became nondirected in the second donation. Seventeen (85%) were nondirected at the second donation. Common reasons for donating the second time were a good experience with the first donation and knowing that one can donate again. Outcomes and the incidence of early complications were not significantly different after the 2nd versus the 1st donation. All donors recovered and currently are doing well. Our results show a significant number of dual organ donors are nondirected and motivated by their strong desire to help. A positive experience with the 1st donation often was the driving factor for the 2nd. A history of previous organ donation did not negatively impact the 2nd donation.